But it does move, doesn´t it? The debate on the allocation of refugees in Europe from a German point of view - Bendel, Petra (Border Crossing Transnational Working Papers, 2015)
This article examines the current debate on the allocation of refugees, based on the principle of “shared responsibility and solidarity among the EU Member States”. Arguing that the Dublin system has failed, I discuss alternative proposals, adopting both the perspective of the Member States and the view of the applicants themselves. Whereas most research has centred on the opportunities and risks of these instruments, on their efficiency or cost-benefit-relation, I ask for the political enforceability of the possible alternatives in the light of changed power relations in the European Parliament, the Commission and the Council. I shall argue that particularly the current perception of the German government might represent a window of opportunity for a policy change.
Keywords: Responsibility and solidarity; allocation of refugees; Dublin system; political enforceability; Germany